271 Synergistic Effect of Berberine and Tea Tree Oil Against Neisseria Gonorrhea, in Vitro T84 Cell Mucosa Model. (1st May 2022) - Cho, M; Wang, L; Chang, F
ABSTRACT: Introduction: Neisseria gonorrhea could spread through oral sex located at the genitals with one who has pharyngeal gonorrhea—and becoming the most common cause of gonorrhea urethritis in the outpatient clinic. Previous studies revealed oral chlorhexidine rinse could reduce the transmission of gonorrhea. However, chlorhexidine gluconate oral rinses may cause: 1) an increase in staining of teeth and other oral surfaces; 2) an increase in calculus formation; and 3) an alteration in taste perception. In literature reviews, tea tree oil-containing mouth rinses are the most common alternative in treating or preventing oral infectious diseases, such as gingivitis. Objective: The study aimed to demonstrate if tea tree oil alone or combines with other safe, natural product extracts are effective and could be a suitable alternative to chlorhexidine in preventing oral gonorrhea from spreading. Methods: We use in vitro T84 cells as mucosa model and Neisseria gonorrhea strain MS11 by testing minimal inhibitory concentration and bacterial adherence, invasion, and transmigration across mucosal layer. In addition, we've tested Berberine, an active alkaloid ingredient extract from Coptis Chinensis, in the absence or presence of the tea tree oil in the MS11 MIC test, epithelial cell viability test using ceftriaxone as control. Results: We found the minimal inhibitory concentration in Tea tree oil, Berberine, and Ceftriaxone in MS11 strain is 0.2%, 5 μg/ml, and 0.0125 μg/ml . However, when combine the Tea tree oil and barberine, the MIC decreased to 0.000625% Tea tree oil + 1.25μg/ml Berberine. The result showed the highest protective effect from tea tree oil with Berberine in the MIC as well as infectivity. No cell death was observed in 0.2% diluted tea tree oil, 5 μg/ml Berberine, and 0.000625% Tea tree oil + 1.25μg/ml Berberine in epithelial cell viability test. Conclusions: Berberine, an alkaloid extract from Coptis Chinensis, shows a synergistic effect when combining with tea tree oil against Neisseria gonorrhea MS11 strain in the T84 cell mucosa model. It may serve as an alternative choice from chlorhexidine gluconate. Disclosure: Work supported by industry: no.